LA RECUELA: ENTRE EL REMAKE Y LA SECUELA. EL CASO DE JURASSIC WORLD - Dra. Irene RAYA BRAVO, (Fonseca, Journal of Communication, 2023)
In the audiovisual field, the expansion of the stories is, specifically, materialized through remakes, adaptations and franchises. In this context, the remakes or new versions are recurrent formulas because they recover familiar contents for audiences and, at the same time, they reinvent it in order to capture new generations’ attention.Nevertheless, the remake formula has been changing in the new millennium, adapting to new narrative trends. In recent years, because of the rise of intertextuality and the increasing value of nostalgia, many films have been produced halfway between the remake and the sequel, such as Star Wars. Episode VII: The Force Awakens or Terminator Genisys. In particular, the aim of this paper is to make a comparative analysis between Jurassic Park and Jurassic World because,although this last film extends the original discourse as a sequel, it also offers a reinterpretation of the first film.